(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2020)
The objective of the study was to evaluate the growth and reproductive performances of Hilly Brown Bengal (HBB) goats of different generations and conducted at Naikhongchari Regional Station Research Farm of Bangladesh Livestock Research Institute. Goats were reared in a plastic slated floor under semi-intensive system and were allowed to graze for 6-7 hours per day. Animals were given a concentrate mixture containing 17% CP, 11 MJ ME/kg DM provided twice daily in the morning and evening at the rate of 1% of their body weight. All goats were kept separately according to sex and age groups to avoid random mating. Natural mating program was performed to improve the economically important traits. Goats were de-wormed and diping on regular intervals and only PPR vaccine was given at the age of 2 months. Data on productive, reproductive and disease incidence of goat were recorded regularly and were analyzed. Results showed that Kid Birth Weight of HBB goats were significantly (P<0.01) differ among generations. Birth weight of G3 (1.21±0.013 kg) was higher than G5, G4, G2 and G1 (1.11±0.01 kg). Goat body weight of 3, 6 and 9 months age were non-significant among generations. The age and weight at first conception were significantly (p<0.05) differ among generation. Age at first conception was lower of G4 (301.57±9.06 days) and higher of G1 (259.80±18.87 days) but body weight at first conception of G1 (12.23±0.47 kg) was higher and G4 was lower (10.65±0.52 kg). Age at first kidding, gestation length and kidding interval was not significant (P>.05) effect on generations. Parity had no significant (P>.05) effect on kid birth weight but significantly (p<0.01) differ of Kid litter weight and litter size. According to birth type single kid was highest birth weight (1.21±0.08 kg) than double kid followed by triplet and quadruplet. Mortality percentage of HBB kids at the age of 0-90 days were 13.08±0.23%. It may be concluded that kid birth weight, age and weight at first conception of HBB goat were significantly (P<.05) affected on generation but age at first kidding, gestation length and kidding interval were non significantly (P<.05) affected. Asian Australas. J. Biosci. Biotechnol. 2020, 5 (2), 72-77